2004
DOI: 10.1080/00365540410019110
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor (HGF) in patients with acute brucellosis

Abstract: In this prospective study, we investigated the serum levels of hepatocyte growth factor (HGF) and C-reactive protein (CRP) before and after the treatment of patients with acute brucellosis. The study comprised 58 patients with acute brucellosis and 30 healthy volunteers. Pre-treatment serum HGF levels of 58 patients with acute brucellosis (1548.6 +/- 220.1) were significantly higher than levels of the control group (401.4 +/- 69.7) (p < 0.001). Serum levels of HGF and CRP significantly decreased at the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
3
1
1
Order By: Relevance
“…That may be explained by Guillén et al 25 who showed that hepatocyte synthesis of CRP is independent from HGF during acute-phase reactions. However, this was contrary to many studies which found a significant positive correlation between them in many infections e.g in pneumonia including being a therapeutic predictor 12 , in acute Brucellosis in which both of them were significantly correlated and significantly declined after treatment 26 .…”
Section: Discussioncontrasting
confidence: 92%
“…That may be explained by Guillén et al 25 who showed that hepatocyte synthesis of CRP is independent from HGF during acute-phase reactions. However, this was contrary to many studies which found a significant positive correlation between them in many infections e.g in pneumonia including being a therapeutic predictor 12 , in acute Brucellosis in which both of them were significantly correlated and significantly declined after treatment 26 .…”
Section: Discussioncontrasting
confidence: 92%
“…Normal koşularda sağlıklı bireylerde serum veya plazmada CRP çok düşük konsantrasyonlarda (100 mg/ml'den küçük) bulunur. İmmünokompetan hastalarda infl amatuar reaksiyonun ya da doku hasarının başlamasından 4-6 saat sonra CRP düzeyi yükselmeye başlar, 24-48 saat içinde zirve değerleri bazal değerlerinin 100-1000 katına çıkar ve yarı ömrü yetişkinlerde yaklaşık 19, yenidoğanlarda 12 saattir (3,9,10). Bakteriyel infeksiyonların akut evresinde CRP düzeyleri orta derece ya da fazla miktarda yükselirken, viral infeksiyonlarda normal ya da hafi f artmış olarak saptanmaktadır (11).…”
Section: İrdelemeunclassified
“…The results of the present study suggest that HGF may also be useful to assess the efficacy of azithromycin administration to MP patients. HGF has previously been used to evaluate the effectiveness of treatment in patients with acute brucellosis and acute myocardial infarction (48,49). Though this suggests that HGF is a general indicator for inflammation or the immune response the results of the present study indicated that HRP had a higher sensitivity and specificity than CRP in assessing efficacy of azithromycin treatment of MP.…”
Section: Mp Severity ------------------------------------------------mentioning
confidence: 50%